The Effects of Mixed Source Fertilizer Application on Vertisol Fertility and Growth of Mustard - Syamsiyah, Jauhari; Sumarno, Sumarno; Suryono, Suryono; Muhamat Rajab, Nur Echsan; Aryaningrum, Ida (UNIVERSITY OF LAMPUNG, 2017)
Soil fertility is a crucial factor determining the growth and yield of plants. The increase of nutrient content and availability in soil can be achieved by fertilization. A field experiment was conducted using a Randomized Completely Block Design (RCBD) with two factors and three replications in order to study the effects of Mixed Source of Fertilizer (MSF) application on the nutrient contents in Vertisol and its relationship to the growth and yield of mustard. The first factor was the three MSF formulas (F1, F2, F3) and second factor was the doses of MSF (0; 2.5; 5.0; 7.5; 10 Mg ha-1) applied to the soil. At the end of the experiment, the soil pH, CEC, organic-C, total-N, available-P and exchangeable-K contents were measured. The results show that there are no significant differences on the soil chemical characteristics, such as pH, organic-C content, available-P, exchangeable-K, -Ca and -Mg measured after application of different MSF formulas to the soil. Meanwhile, the increase of MSF doses applied to the soil significantly increases organic-C content, total-N, available-P and exchangeable-K in the soil. The significant increase of available-P (by 29.13%) and total-N (by 24.1%) occured after application of MSF at 5.0 Mg ha-1 and the increase of exchangeable-K (by 50%) is achieved after application of 7.5 Mg ha-1, in comparison to that without MSF application. The height and fresh weight of mustard increase in accordance with the increase of MSF doses applied. The application of 10.0 Mg ha-1 MSF results in the highest height and fresh weight of the mustard up to 63.9% and 620%, respectively. The height and fresh weight of mustard are positively correlated to the total-N, available-P and exchangeable-K in the soil. The MSF is an alternative fertilizer that can be used to improve Vertisol fertility and plant growth.Â